How faculty recruitment shaped economic culture: the case of Italy 1900–1942. Issue 2 (14th March 2016) - Barucci, Piero; Misiani, Simone; Mosca, Manuela
Abstract : This article belongs to the area of university policy, viewed as an important example of the relationship between culture and power. As a case study, it utilizes the competitive exams for university chairs which took place in Italy for economic disciplines between 1900 and 1942. Interpreting the rules, the criteria and the outcomes of faculty recruitment, the article reconstructs an overall picture of the actors, themes and orientations, as well as the channels used to spread ideas. In this way, it clarifies important aspects of the influence exercised by the political sector over economic culture prior to and during fascism, in particular, in the formation of a consensus for government intervention in the Italian economy.